Mergers and acquisition law: the need for harmonization in ASEAN - Ambaras Khan, Mushera Bibi; Abdul Ghani Azmi, Ida Madieha; Abdul Rahman, Nasarudin; Zakaria, Mohd Radhuan Arif (Universitas Muhammadiyah Yogyakarta, 2017)
The topic of mergers and acquisitions continues to receive significant attention from both academic and practical perspectives. The growing incidence of company takeovers, especially cross-border, raises significant policy concerns. The sustainability of companies domestically and globally has thus become a major concern. There is a dire need for law to offer an avenue to allow an efficient and competitive environment for mergers and acquisition of companies. Cross-border mergers and acquisition activities have also increased in the current years, with a greater share of ASEAN firms in total acquisitions. With the introduction of ASEAN common market, ASEAN countries are now a more open, transparent and convenient investment regime which facilitate international trade and foreign investment. A comprehensive and effective legal framework for mergers and acquisitions is imperative to support the burgeoning of mergers and acquisitions as a result of the liberalization of the trade and services in the ASEAN countries. This paper suggest that harmonization of the law is inevitable in order to support the growing of mergers and acquisitions in the region. This paper suggests that a more consistent and uniform frameworks are needed to reduce restrictive regulations which may inhibit the mergers and acquisition deals in the ASEAN.